The Development of Science Learning Activities by Applying the STEM Education Model to Promote Student Creativity - Sonthong, Wanwisa; Intanin, Angkhan; Sanpundorn, Sasitorn (International Journal of Research in STEM Education, 2023)
This research aimed to design and evaluate science learning activities using the STEM education model to foster creativity among students. Employing a type I developmental methodology, the study was structured into two primary phases: development and evaluation. In the development phase, contemporary educational challenges were identified, leading to the formulation of STEM-based learning activities, which were then tested with a select group of students. For the sample, a distinct student group participated in these STEM activities, with their creativity and satisfaction becoming the central assessment metrics. Results revealed a formulated STEM education model with five essential steps: introduction, problem identification, information gathering, solution design and implementation, and presentation. Following the activities, students' creativity scores averaged at 86.16%, surpassing the target of 80%. Additionally, satisfaction feedback indicated a high average rating of 4.65. To conclude, the customized STEM education model effectively heightened creativity among students, evident from their elevated creativity scores and significant satisfaction rates. Recommendations from this study urge schools and educational institutions to adopt this STEM education model due to its demonstrated efficacy in boosting student creativity and satisfaction, offering a structured methodology to tackle existing educational challenges and stimulate innovation.